Peran Job Insecurity terhadap Stres Kerja dengan Moderator Religiusitas - Muhammad Farid Bashori; IJK Sito Meiyanto (Gadjah Mada Journal of Psychology (GamaJoP), 2017)
Stress is one of the psychological reactions that can be in a work situation. Work situations may change at any time in different forms. An employee's psychological reaction to change also varies. Job insecurity arising from changing work situations increases job stress. A company certainly does not want employees to experience work stress that can impact on the decline in company performance. The level of employeereligiosity is expected to reduce the impact of job insecurity. This study aims to determine the role of job insecurity against work stress moderated by religiosity. Job stress as the dependent variable, job insecurity as an independent variable, and religiosity as moderator. Methods of data retrieval were performed using work stress scale, job insecurity scale, and scale of religiosity. The subjects of this study were 119 employees working in the State Forestry Corporation. The hypothesis proposed in this study is religiosity as a moderator in the relationship between job insecurity with work stress. Moderate and hypothesis testis done by moderate regression analysis. The research result shows religiosity not proved as moderator in the relationship between job insecurity with work stress, but the directly significant impact to work.